2020 China Conference: Taking Action for the World's Poor - International Food Policy Research Institute (2007)
Concerned that millions of the world's poorest and hungry people remain in poverty and hunger, the International Food Policy Research Institute (IFPRI) facilitated a consultation process, which includes the conference "Taking Action for the World's Poor and Hungry People" on October 17-19 in Beijing, to examine what new and different action is required to improve their welfare.